Transcriptomic and metabolomic analysis of carotenoid metabolism and accumulation of carotenoid-derived products in tobacco leaves before and after curing - Liu, Tao; Kong, Na; Cao, Jianmin; Chen, Gang; Deng, Zhichao; Wen, Lichao; Zhang, Zhenbiao; Guo, Cun; Wu, Rongrong; Yang, Yalun; Li, Wei; Guo, Yongfeng (Frontiers in Plant Science, 2025)
As an important cash crop, tobacco (Nicotiana tabacum L.) is grown to harvest leaves which are cured at elevated temperature before sale. The quality of cured leaves impacts the economic return of growers. High-quality tobacco has high levels of aroma substances in cured leaves, derived mainly from carotenoid degradation products (CDPs). Significant difference in CDPs levels occurs between varieties of distinct genetic background and between regions with different ecological conditions. In order to have a better understanding of what are the major factors that influence the accumulation of CDPs in tobacco leaves, four tobacco varieties, K326, NC82, G28, and Gexin3, with different aroma characteristics, were grown in two typical fields in Shandong and Yunnan, two major tobacco-producing areas in northern and southern China, respectively. Transcriptomic and metabolomic analysis was conducted to identify differentially expressed genes and metabolites. The results of transcriptome analysis revealed that the number of differentially expressed genes (DEGs) between the two locations was more than three times of that among varieties, with the DEGs between locations enriched in the carotenoid biosynthetic pathway. For fresh leaves, similar group of carotenoid-related DEGs were identified and more significant difference in carotenoid contents was observed between locations than among varieties, with higher carotenoid accumulation in tobacco grown in Shandong. Significant decrease in carotenoid contents in leaves was observed during the curing process after harvest. For the same variety, the reduction in carotenoid content following curing was greater in Shandong than in Yunnan. The accumulation of CDPs in tobacco leaves after curing, however, appeared to be complex, being influenced by both environmental and genetic factors. Among the detected CDPs, acetoin, geranyl acetone, and megastigmatrienone were primarily affected by environmental factors, whereas β-ionone-5,6-epoxyde and 3-oxo-α-ionol were predominantly influenced by genetic factors. This study systematically reveals the cascade regulatory relationship among “gene expression – carotenoid accumulation – aroma formation”.